Maximize The Use of Internet To Improve Sales of Small Businesses: Evidence from Indonesia - Isferianto Ruswandi,; R A Khaeru Ahmadi, (Technium Social Sciences Journal, 2023)
In today's digital era, businesses must harness the internet’s full potential to improve their sales and remain competitive. Unfortunately, not all small businesses in Indonesia can improve their sales on internet. An official survey by APJII (Indonesia Internet Service Provider Association) found that estimates of sales growth of small businesses using the internet are not maximal, and some of them haven’t grown in sales. On the other side, case studies showcasing successful internet-driven sales technique implementations. Therefore, this study analyzes how small businesses can maximize internet use to optimize their sales performance and explores strategies and best practices. A comprehensive analysis of literature, secondary data, usage and user behavior of the internet in Indonesia was used. By understanding and applying the insights presented in this research, small businesses have the ability to take advantage of the internet and achieve considerable increases in their sales figures.